Conductive film and method for forming same
By adding unreduced copper oxide particles and specific binding agents to form an unreduced unreduced layer during the conductive film formation process, the problem of insufficient adhesion of the conductive film to the substrate is solved, and the combination of high adhesion and high conductivity is achieved.
Patent Information
- Application Number
- JP2024184662
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2023-11-07
- Filing Date
- 2024-10-21
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2044-10-21
AI Technical Summary
The conductive film formed in the prior art lacks adhesion to the substrate, especially when using a substrate material that is susceptible to heat, such as paper, it is difficult to form a conductive film with high conductivity at a short time at a low temperature.
During the formation of the conductive film, unreduced copper oxide particles and a specific content of binder are added to form an unreduced unbound layer. The carbon mole fraction of the copper oxide particles and binder is between 0.15% and 0.9% and the oxygen mole fraction is between 0.03% and 0.2%.
By forming an unreduced unjunctioned layer, the adhesion of the conductive film to the substrate is significantly improved while maintaining the high conductivity of the conductive film.
Smart Images

Figure 0007663768000004 
Figure 0007663768000001 
Figure 0007663768000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a conductive film and a method for forming a conductive film. [Background technology]
[0002] With the spread of IC tags and the like, a technology for forming a conductive film not only on polyethylene terephthalate (PET) film but also on paper and the like has been developed. In particular, in the case of a substrate such as paper, in order to minimize the influence of heat on the substrate, it is required to form a conductive film by heating at a low temperature for a shorter period of time, and it is also required to have the same conductivity as a conductive film formed by heating at a high temperature. As a method for forming such a conductive film, for example, a technology is known in which a photo-sintered composition containing cuprous oxide particles, a solvent, and a binder resin is applied to a substrate to form a coating film, and the coating film is irradiated with light to reduce the cuprous oxide particles in the coating film to copper, thereby forming a conductive film (see Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2019-149360 A [Patent Document 2] JP 2019-200912 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the conductive films formed by the techniques described in Patent Documents 1 and 2 have a problem in that they have insufficient adhesion to the substrate.
[0005] Therefore, an object of the present invention is to provide a conductive film having excellent adhesion to a substrate and a method for forming the same. [Means for solving the problem]
[0006] Means for Solving the Problems The inventors of the present invention have conducted intensive research in light of the above-mentioned circumstances, and as a result have discovered that the above-mentioned problems can be solved by providing an unsintered layer containing cuprous oxide particles and a specific binder resin that remain without being photoreduced between a substrate and a conductive film made of a photoreduced sintered product of a composition containing cuprous oxide particles and a specific binder resin, and have thus completed the present invention.
[0007] That is, the present invention provides a conductive film formed on a substrate, the conductive film comprising a photoreduced sintered product of a composition containing cuprous oxide particles and a binder resin, an unsintered layer containing cuprous oxide particles and binder resin that have not been photoreduced and remain is formed between the substrate and the conductive film, and the carbon molar fraction in the binder resin molecule is 0.15% to 0.9%, and the oxygen molar fraction is 0.03% to 0.2%. The present invention also provides a method for forming a conductive film on a substrate, the method comprising the steps of: applying a composition containing cuprous oxide particles and a binder resin to the substrate to form a coating film; and irradiating the coating film with light to photo-reduce and sinter the cuprous oxide particles in the coating film to form a conductive film, while forming an unsintered layer between the substrate and the conductive film, the unsintered layer containing the cuprous oxide particles and the binder resin that have not been photo-reduced, the binder resin having a carbon molar fraction of 0.15% to 0.9% and an oxygen molar fraction of 0.03% to 0.2% in the molecule of the binder resin. Effect of the Invention
[0008] According to the present invention, it is possible to provide a conductive film having excellent adhesion to a substrate and a method for forming the same. [Brief description of the drawings]
[0009] [Figure 1] 1 shows an SEM image and EDS element mapping images of copper, oxygen, and carbon elements of a cross section of a conductive film formed on a substrate in Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The conductive film according to one embodiment of the present invention is formed on a substrate and is made of a photoreduced sintered product of a composition containing cuprous oxide particles and a binder resin. Between the substrate and the conductive film, an unsintered layer containing cuprous oxide particles and binder resin that have not been photoreduced is formed, and the carbon molar fraction in the molecule of the binder resin is 0.15% to 0.9% and the oxygen molar fraction is 0.03% to 0.2%. In the conductive film according to one embodiment of the present invention, a predetermined unsintered layer is provided between the substrate and the conductive film, ensuring excellent conductivity, while the binder resin in the unsintered layer exerts an adhesive effect to improve the adhesion between the substrate and the conductive film. As described above, the unsintered layer contains cuprous oxide particles and binder resin that have not been photoreduced, but some of the cuprous oxide particles may contain a small amount of copper that has been photoreduced. From the viewpoint of improving adhesion to various substrates while ensuring excellent conductivity, the ratio of the thickness of the conductive film to the thickness of the unsintered layer after compression treatment is preferably 10:90 to 98:2, and more preferably 20:80 to 90:10. If the ratio of the conductive film to the thickness of the unsintered layer is smaller than 10:90, it is difficult to obtain sufficient conductivity, and if the ratio of the conductive film to the thickness of the unsintered layer is larger than 98:2, it may be difficult to obtain the effect of adhesion due to the unsintered layer. In one embodiment of the present invention, the cross section of the conductive film formed on the substrate after compression treatment is subjected to EDS element mapping analysis of copper, oxygen, and carbon elements using a scanning electron microscope (SEM), and the boundary between the substrate and the unsintered layer and the boundary between the conductive film and the unsintered layer are determined, and the thickest points of the conductive film and the unsintered layer are identified from these boundaries, and these are taken as the thicknesses of the conductive film and the unsintered layer, respectively.
[0011] The cuprous oxide particles used in one embodiment of the present invention are not particularly limited as long as they are reduced to copper by irradiation with light, and commercially available products may be used. The method for producing the cuprous oxide particles is not particularly limited. The shape of the cuprous oxide particles is not particularly limited, and may be any of spherical, polyhedral, and amorphous. From the viewpoint of excellent handling and photosintering properties, the average primary particle diameter of the cuprous oxide particles is preferably 1 nm to 2000 nm, more preferably 15 nm to 500 nm, and even more preferably 30 nm to 300 nm. The average primary particle diameter of the cuprous oxide particles in one embodiment of the present invention is obtained by measuring the primary particle diameter of each of 50 cuprous oxide particles selected arbitrarily in an image of the cuprous oxide particles observed with a scanning electron microscope (SEM), and arithmetically averaging the values.
[0012] From the viewpoint of suppressing an increase in viscosity of the composition and forming a conductive film of sufficient thickness, the cuprous oxide particles are preferably contained in an amount of 3 mass % to 95 mass %, and more preferably 5 mass % to 85 mass %, relative to the composition.
[0013] The cuprous oxide particles used in one embodiment of the present invention preferably contain at least one additive element selected from the group consisting of tin, manganese, vanadium, cerium, and silver, from the viewpoint of easily forming a conductive film with few defects and uniformity. The preferred content of the additive element varies depending on the type of additive element, but may be within the range of 1 ppm to 30,000 ppm. When the additive element is tin, from the viewpoint of controlling the solubility of tin ions and the particle size of the cuprous oxide particles, the content is preferably 1 ppm to 30,000 ppm, more preferably 10 ppm to 10,000 ppm, and even more preferably 150 ppm to 3,000 ppm. When the additive element is manganese, from the viewpoint of controlling the solubility of manganese ions and the particle size of the cuprous oxide particles, the content is preferably 10 ppm to 20,000 ppm, more preferably 30 ppm to 10,000 ppm, and even more preferably 100 ppm to 8,000 ppm. When the additive element is vanadium, from the viewpoint of controlling the solubility of vanadium ions and the particle size of cuprous oxide particles, the content is preferably 10 ppm to 20000 ppm, more preferably 30 ppm to 10000 ppm, and even more preferably 100 ppm to 8000 ppm. When the additive element is cerium, from the viewpoint of controlling the solubility of cerium ions and the particle size of cuprous oxide particles, the content is preferably 10 ppm to 30000 ppm, more preferably 30 ppm to 20000 ppm, and even more preferably 10 ppm to 10000 ppm. When the additive element is silver, from the viewpoint of controlling the solubility of silver ions and the particle size of cuprous oxide particles, the content is preferably 1 ppm to 30000 ppm, more preferably 5 ppm to 20000 ppm, and even more preferably 10 ppm to 10000 ppm. Among these additive elements, tin is preferred from the viewpoint of low melting point and low resistance. In the present invention, the content of the added element in the cuprous oxide particles is a value obtained by dissolving 1 g of cuprous oxide in 10 ml of concentrated hydrochloric acid and measuring the solution using an ICP emission spectrometer (ICPS-8100 manufactured by Shimadzu Corporation).
[0014] The cuprous oxide particles containing the above-mentioned additive element can be produced, for example, by mixing an aqueous solution containing copper ions and at least one additive ion selected from the group consisting of divalent tin ions, divalent manganese ions, tetravalent vanadium ions, trivalent cerium ions, and monovalent silver ions with an alkaline solution to generate copper hydroxide, and then adding a reducing agent to reduce and precipitate the cuprous oxide particles. When generating copper hydroxide and reducing and precipitating the cuprous oxide particles, it is preferable to stir the reaction solution so that the reaction solution is homogeneous. The average primary particle size of the cuprous oxide particles can be adjusted by conditions such as the concentration of the additive ions during the production of the cuprous oxide particles and the mixing temperature of the copper ion-containing aqueous solution and the alkaline solution.
[0015] As the copper ion source contained in the aqueous solution, inorganic copper compounds such as copper chloride, copper sulfate, copper nitrate, copper cyanide, copper thiocyanate, copper fluoride, copper bromide, copper iodide, copper carbonate, copper phosphate, copper borofluoride, copper hydroxide, copper pyrophosphate, organic copper compounds such as copper acetate and copper lactate, and hydrates thereof can be used. These copper ion sources may be used alone or in combination of two or more. Among these copper ion sources, it is preferable to use copper chloride and copper sulfate from the viewpoint of high solubility in water and low cost. The copper ion concentration in the aqueous solution is preferably 0.1 mol / L to 2 mol / L from the viewpoint of reaction efficiency.
[0016] At least one added ion selected from the group consisting of divalent tin ions, divalent manganese ions, trivalent and tetravalent vanadium ions, trivalent cerium ions, and monovalent silver ions contained in the aqueous solution has the effect of reducing the average primary particle size of the resulting cuprous oxide particles and improving the reduction sintering property to copper. As a divalent tin ion source, inorganic tin compounds such as tin chloride (II), tin sulfate (II), tin oxide (II), tin fluoride (II), tin bromide (II), and tin iodide (II), organic tin compounds such as tin acetate (II), and hydrates thereof can be used. These may be used alone or in combination of two or more. As a divalent manganese ion source, inorganic manganese compounds such as manganese sulfate (II), manganese chloride (II), and manganese nitrate (II), organic manganese compounds such as manganese acetate (II), and hydrates thereof can be used. These may be used alone or in combination of two or more. As the tetravalent vanadium ion source, inorganic vanadium compounds such as vanadium oxide sulfate (IV), vanadium tetrachloride (IV), vanadium oxide hydrochloride (IV), vanadium chloride (III), vanadium oxide (III), vanadium oxide (IV), organic vanadium compounds such as vanadium tetraacetate (IV), hydrates thereof, etc. can be used. These may be used alone or in combination of two or more. As the trivalent cerium ion source, inorganic cerium compounds such as cerium chloride (III), cerium oxide (III), cerium nitrate (III), cerium sulfate (III), cerium fluoride (III), cerium bromide (III), cerium iodide (III), organic cerium compounds such as cerium oxalate (III), cerium acetate (III), hydrates thereof, etc. can be used. These may be used alone or in combination of two or more.As the monovalent silver ion source, inorganic silver compounds such as silver chromate (I), silver dichromate (I), silver oxide (I), potassium dicyanoargentate (I), silver cyanide (I), silver bromide (I), silver nitrate (I), silver selenate (I), silver tungstate (I), silver carbonate (I), silver thiocyanate (I), silver telluride (I), silver fluoride (I), silver molybdate (I), silver iodide (I), silver sulfide (I), silver sulfate (I), silver phosphate (I), silver diphosphate (I), silver nitrite (I), silver isocyanate (I), silver chloride (I), and silver perchlorate (I), organic silver compounds such as silver citrate (I), silver acetate (I), silver lactate (I), silver formate (I), and silver benzoate (I), and their hydrates can be used. These may be used alone or in combination of two or more. The concentration of the added ions in the aqueous solution is not particularly limited as long as the content of the added elements in the finally obtained cuprous oxide particles is within the above-mentioned preferred range, but from the viewpoint of being easily incorporated into the cuprous oxide as a co-deposit and facilitating photosintering of the co-deposit, it is preferable that the concentration is 0.001 mol to 0.1 mol per mol of copper ions. The average primary particle size of the finally obtained cuprous oxide particles can be controlled by changing the concentration of the added ions. Specifically, the average primary particle size of the cuprous oxide particles can be reduced by increasing the concentration of the added ions.
[0017] As the alkaline solution, a common solution in which an alkali such as sodium hydroxide, potassium hydroxide, lithium hydroxide, or the like is dissolved in water can be used. From the viewpoint of controlling the particle size of the cuprous oxide particles finally obtained and controlling the reduction reaction, the concentration of the alkali is preferably an amount of 0.1 mol to 10 mol per mol of copper ions contained in the copper ion-containing aqueous solution to be mixed with the alkaline solution.
[0018] The reaction temperature when the copper ion-containing aqueous solution is mixed with the alkaline solution to generate copper hydroxide is not particularly limited, but may be 10°C to 100°C, and is preferably 30°C to 95°C from the viewpoint of reaction control. The average primary particle size of the cuprous oxide particles finally obtained can be controlled by changing the reaction temperature. Specifically, the average primary particle size of the cuprous oxide particles can be increased by increasing the reaction temperature. The reaction time is not particularly limited, but may be more than 0 minutes to 120 minutes or less, since copper hydroxide is generated immediately after mixing depending on the concentration of copper ions, the type and concentration of the alkaline solution, and the reaction temperature. If the reaction time exceeds 120 minutes, copper oxide is gradually generated from copper hydroxide due to the action of the added ions.
[0019] As the reducing agent, glucose, fructose, maltose, lactose, hydroxylamine sulfate, hydroxylamine nitrate, sodium sulfite, sodium hydrogen sulfite, sodium dithionite, hydrazine, hydrazine sulfate, hydrazine phosphate, hypophosphorous acid, sodium hypophosphite, sodium borohydride, etc. can be used. Among these reducing agents, reducing sugars such as glucose and fructose are preferred from the viewpoints of being inexpensive, easily available, easy to handle, and having a high reduction efficiency to cuprous oxide. The amount of the reducing agent to be added is preferably 0.1 to 10 moles per mole of copper ions from the viewpoint of controlling the reduction reaction from copper hydroxide to cuprous oxide.
[0020] The reaction temperature during reduction and precipitation is not particularly limited, but may be 10° C. to 100° C., and from the viewpoint of reaction control, is preferably 30° C. to 95° C. The reaction time here is not particularly limited, but may usually be 5 minutes to 120 minutes.
[0021] The slurry containing the precipitated cuprous oxide particles is filtered and washed with water to obtain a cuprous oxide cake. Examples of the filtration and washing methods include a method of washing the particles while the particles are fixed by a filter press or the like, a method of decanting the slurry, removing the supernatant, adding pure water, stirring, and then decanting again to remove the supernatant, and a method of repeating the operation of repulping the filtered cuprous oxide particles and filtering again. The obtained cuprous oxide particles may be subjected to an antioxidant treatment as necessary. For example, an antioxidant treatment is performed using organic substances such as sugars, polyhydric alcohols, rubber, heptone, carboxylic acids, phenols, paraffin, and mercaptans, and inorganic substances such as silica, and then the obtained cuprous oxide cake is dried in an atmosphere and at a temperature (for example, under vacuum, 30°C to 150°C) that does not reduce the cuprous oxide to copper and does not oxidize the cuprous oxide to copper oxide, thereby obtaining cuprous oxide particles. The obtained cuprous oxide particles may also be subjected to a treatment such as crushing and sieving as necessary.
[0022] The binder resin used in one embodiment of the present invention may have a carbon molar fraction in the molecule of 0.15% to 0.9% and an oxygen molar fraction of 0.03% to 0.2%. When the carbon molar fraction and oxygen molar fraction in the molecule of the binder resin are within the above ranges, the cuprous oxide particles present in the surface layer of the coating film formed by applying the composition to the substrate are reduced, and the binder resin present in the surface layer is gasified and disappears, forming a conductive film with high continuity and low resistance, while the binder resin present in the lower layer of the coating film is likely to remain, and this remaining binder resin is thought to improve the adhesion between the conductive film and the substrate. If the carbon molar fraction in the molecule of the binder resin is too small, the reduction of the cuprous oxide particles present in the surface layer of the coating film formed by applying the composition to the substrate is difficult to proceed, and if the light irradiation energy is increased to proceed with the reduction, defects such as scattering, peeling, and cracking of the conductive film will occur. On the other hand, if the carbon molar fraction in the binder resin molecule is too large, the light irradiation energy is used for the oxidation of carbon, and the amount of CO and CO2 gas increases, resulting in defects such as scattering, peeling, and cracking of the conductive film. Also, if the oxygen molar fraction in the binder resin molecule is too small, the amount of CO and CO2 gas generated by the reduction of the cuprous oxide particles increases, resulting in defects such as scattering, peeling, and cracking of the conductive film. On the other hand, if the oxygen molar fraction in the binder resin molecule is too large, the reduction of the cuprous oxide particles becomes difficult to proceed, and if the light irradiation energy is increased to proceed with the reduction, defects such as scattering, peeling, and cracking of the conductive film occur. From the viewpoint of improving adhesion while ensuring excellent conductivity, it is preferable that the carbon molar fraction in the binder resin molecule is 0.20% to 0.80% and the oxygen molar fraction is 0.05% to 0.18%. The carbon molar fraction and oxygen molar fraction in one embodiment of the present invention are values measured using an organic elemental analyzer vario EL cube manufactured by Elementar.
[0023] The binder resin used in one embodiment of the present invention preferably has a 50% weight loss temperature of 300°C to 500°C, from the viewpoints that excess binder resin is unlikely to remain in the conductive film after light irradiation, thereby realizing low resistance of the conductive film, and also easily ensuring adhesion between the substrate and the conductive film.
[0024] Specific examples of the binder resin include cellulose resin, polyvinyl resin, unsaturated polyester resin, saturated polyester resin, terpene phenol resin, acrylic resin, polyurea resin, polyurethane resin, polyether resin, epoxy resin, chlorinated polyolefin resin, epoxy acrylate resin, phenol resin, melamine resin, alkyd resin, etc. These binder resins may be used alone or in combination of two or more. Since the binder resin is usually dissolved in an organic solvent for use, it is sufficient to select from the above-mentioned binder resins one that satisfies the above-mentioned carbon molar fraction and oxygen molar fraction and dissolves in an organic solvent. From the viewpoint of easily forming a conductive film without defects and further improving the adhesion between the conductive film and the substrate, the binder resin is preferably at least one selected from the group consisting of cellulose resin, polyvinyl resin, unsaturated polyester resin, saturated polyester resin, terpene phenol resin, acrylic resin, polyurea resin, polyurethane resin, polyether resin, and epoxy resin.
[0025] Examples of cellulose resins include methyl cellulose, ethyl cellulose, propyl cellulose, carboxymethyl cellulose, carboxyethyl cellulose, carboxypropyl cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose. Examples of polyvinyl resins include polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride, and polyvinylphenol. Examples of unsaturated polyester resins include polymerized unsaturated polyesters obtained by reacting unsaturated polybasic acids such as maleic acid, fumaric acid, and itaconic acid with polyhydric alcohols such as ethylene glycol and propylene glycol. Examples of saturated polyester resins include polyethylene terephthalate, polyethylene isodylate, and polybutylene terephthalate. Examples of terpene phenol resins include hydrogenated terpene phenol resins. Examples of acrylic resins include polymethyl (meth)acrylate, polyethyl (meth)acrylate, and polypropyl (meth)acrylate. Examples of polyether resins include polyethylene glycol and polypropylene glycol. Examples of epoxy resins include phenol novolac type epoxy resins, triphenylmethane type epoxy resins, bisphenol A type epoxy resins, biphenyl type epoxy resins, etc. From the viewpoint of easily forming a conductive film without defects and further improving the adhesion between the conductive film and the substrate, the binder resin is preferably at least one selected from the group consisting of methyl cellulose, ethyl cellulose, polyvinyl pyrrolidone, polyvinyl alcohol, polyvinyl acetate, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyethylene glycol, and polypropylene glycol.
[0026] From the viewpoint of preventing excess binder resin from remaining in the conductive film after light irradiation and facilitating the securing of adhesion between the substrate and the conductive film, the content of the binder resin is preferably 0.5% by mass to 20% by mass, and more preferably 1% by mass to 15% by mass, relative to the composition.
[0027] In one embodiment of the present invention, the composition has a viscosity of 1.0×10 at 20° C. from the viewpoint of further improving the uniformity of the conductive film. -3 The metal particles may further include metal particles having a volume resistivity of Ω·cm or less. The metal species of such metal particles is gold (volume resistivity at 20° C.: 2.4×10 -6 Ω cm), silver (volume resistivity at 20°C: 1.6×10 -6 Ω cm), copper (volume resistivity at 20°C: 1.7×10 -6 Ω cm), zinc (volume resistivity at 20°C: 5.9×10 -6 Ω cm), tin (volume resistivity at 20°C: 11.4×10 -6 Ω cm), aluminum (volume resistivity at 20°C: 2.75×10 -6 Ω cm), Nickel (volume resistivity at 20°C: 7.2×10 -6 Ω cm), cobalt (volume resistivity at 20°C: 6.4×10 -6 Ω cm) and manganese (volume resistivity at 20°C: 48×10 -6 Among these metal particles, copper particles are preferred from the viewpoints of good conductivity and low cost. Two or more of these metal particles may be used in combination, and the metal particles may have a specific surface area of 1.0×10 at 20° C. or less. -3 Alloy particles having a volume resistivity of Ω·cm or less may be used.
[0028] From the viewpoint of ease of handling and photosintering, the average primary particle size of the metal particles is preferably 10 nm to 50 μm, and more preferably 50 nm to 10 μm. The average primary particle size of the metal particles in one embodiment of the present invention is obtained by measuring the primary particle size of each of 50 arbitrarily selected particles in an image observed with a scanning electron microscope (SEM) and arithmetically averaging the values. The shape of the metal particles is not particularly limited, and may be any of spherical, polyhedral, flaky, amorphous, agglomerated powder, and mixtures thereof.
[0029] When the composition contains the above-mentioned metal particles, from the viewpoints of suppressing an increase in the viscosity of the composition and forming a conductive film of sufficient thickness, the total of the cuprous oxide particles and the metal particles is preferably 10% by mass to 95% by mass, and more preferably 20% by mass to 85% by mass, relative to the composition. From the viewpoints of preventing scattering during sintering, sinterability of the conductive film, and adhesion to the base material, the mass ratio of the metal particles to the cuprous oxide particles contained in the composition according to one embodiment of the present invention is preferably 95:5 to 5:95, and more preferably 90:10 to 10:90.
[0030] The organic solvent is not limited as long as it can disperse the cuprous oxide particles and the metal particles and dissolve the binder resin. Specific examples of the organic solvent include methanol, ethanol, propanol, isopropyl alcohol, isobutanol, 1,3-propanediol, 1,2,3-propanetriol (also known as glycerin), ethylene glycol, diethylene glycol, triethylene glycol, dipropylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monopropyl ether, diacetone alcohol, ethylene glycol monobutyl ether, propylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, dipropylene glycol monopropyl ether, and the like. Examples of organic solvents include propyl ether, butyl carbitol (also known as diethylene glycol monobutyl ether), tripropylene glycol, triethylene glycol monoethyl ether, terpineol, dihydroterpineol, dihydroterpinyl monoacetate, methyl ethyl ketone, cyclohexanone, ethyl lactate, propylene glycol monomethyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene glycol monobutyl ether acetate, ethylene glycol monomethyl ether acetate, ethylene glycol monobutyl ether acetate, dibutyl ether, octane, and toluene. These organic solvents may be used alone or in combination of two or more. Among these organic solvents, terpineol and butyl carbitol are preferred from the viewpoints of drying property and viscosity of the coating film, dispersibility of cuprous oxide particles and metal particles, solubility of binder resin, and the like.
[0031] From the viewpoints of suppressing an increase in viscosity of the composition, ease of handling, and photosintering properties, the organic solvent is preferably contained in an amount of 5 to 80% by mass, and more preferably 10 to 70% by mass, based on the composition.
[0032] The composition according to one embodiment of the present invention may contain additional components other than the above-mentioned cuprous oxide particles, binder resin, metal particles, and solvent. Examples of such additional components include dispersants, protective agents, viscosity modifiers, anti-settling agents, thixotropy-imparting agents, reducing agents, agents for compatibility with the substrate on which the conductive film is to be formed, sintering aids, etc. However, these additional components are preferably substances that are volatilized in the drying process or gasified and removed in the photo-reduction sintering process, and more preferably compounds composed of carbon, hydrogen, oxygen, and nitrogen.
[0033] The material of the substrate on which the conductive film is formed is not particularly limited, but examples thereof include resins such as polyethylene terephthalate, polyimide, polyethylene naphthalate, etc.; glasses such as quartz glass, soda glass, non-alkali glass, etc.; metals such as iron, copper, aluminum, etc.; semi-metals such as silicon, germanium, etc.; ceramics such as alumina, zirconia, silicon nitride, silicon carbide, etc.; paper, etc. In the conductive film forming method according to one embodiment of the present invention, a conductive film can be formed by heating at a low temperature for a shorter period of time, and therefore, it is suitable for forming a conductive film on a paper substrate.
[0034] The conductive film according to one embodiment of the present invention is suitable for applications such as IC tags, electromagnetic shields, wiring materials for electronic circuit boards, mesh electrodes, heat dissipation materials, and the like.
[0035] A method for forming a conductive film according to one embodiment of the present invention includes the steps of applying the above-described composition to a substrate to form a coating film, and irradiating the coating film with light to photo-reduce and sinter the cuprous oxide particles in the coating film to form a conductive film, while forming an unsintered layer between the substrate and the conductive film, the cuprous oxide particles remaining without being photo-reduced and the binder resin remaining without being gasified.
[0036] The method of applying the composition to the substrate may be selected appropriately depending on the viscosity of the composition, the average primary particle size of the cuprous oxide particles and the metal particles, etc. Specific application methods include, for example, bar coating, spray coating, spin coating, dip coating, roll coating, inkjet printing, gravure printing, screen printing, etc. The thickness of the coating may be appropriately determined depending on the thickness of the desired conductive film, but is preferably 0.1 μm to 100 μm from the viewpoints of sinterability and adhesion.
[0037] The method for forming a conductive film according to one embodiment of the present invention preferably further comprises a step of drying the coating film after the coating film is formed. By removing the organic solvent remaining in the coating film by drying, it is possible to reduce the occurrence of defects in the conductive film in the photoreduction baking step described below. A known dryer such as an air blower dryer or a warm air dryer can be used to dry the coating film. The drying conditions for the coating film are usually 60°C to 120°C and 5 minutes to 60 minutes.
[0038] In order to reduce and sinter the cuprous oxide particles in the coating film to copper, the coating film may be irradiated with light using a known light irradiation device. The light irradiation is preferably pulsed light irradiation from the viewpoint of easy temperature control. Pulsed light irradiation using a flash lamp is preferable, and pulsed light irradiation using a xenon (Xe) flash lamp is more preferable. Examples of devices capable of performing such pulsed light irradiation include the S-series xenon pulsed light irradiation device manufactured by Xenon Corporation and the Pulse Forge series light baking device manufactured by Novacentrix. In particular, the S-2300 manufactured by Xenon Corporation can set a simple pulsed light of voltage 1 / pulse width 1 with one pulsed light, and further has a function of setting voltage 2 / pulse width 2 continuously after voltage 1 / pulse width 1 with one pulsed light, so that continuous pulsed light irradiation of two or more steps with different conditions is possible. In this way, the S-2300 manufactured by Zenon Corporation is suitable for reduction sintering of cuprous oxide particles because it can adjust the irradiation energy for reduction sintering. The number of steps is not particularly limited as long as it can reduce and sinter the cuprous oxide particles present in the surface layer of the coating film and leave the cuprous oxide particles and binder resin present in the lower layer of the coating film, and multiple steps may be set.
[0039] The irradiation energy and pulse width of the pulsed light can be appropriately selected according to the average primary particle size of the cuprous oxide particles, the type and concentration of the binder resin, the type and concentration of the organic solvent, the thickness of the coating film, etc., so that the cuprous oxide particles present in the surface layer of the coating film can be reduced and sintered, and the cuprous oxide particles and binder resin present in the lower layer of the coating film can be left behind. Specifically, from the viewpoint of sufficiently reducing and sintering the cuprous oxide particles present in the surface layer of the coating film, leaving the cuprous oxide particles and binder resin present in the lower layer of the coating film, and reducing damage to the substrate, the cumulative pulsed light irradiation energy is 0.001 J / cm 2 ~100J / cm 2 is preferably 0.01 J / cm 2 ~30J / cm 2The pulse width of the pulsed light is preferably 1 μsec to 100 msec, and more preferably 10 μsec to 10 msec, from the viewpoints of sufficiently reducing and sintering the cuprous oxide particles present in the surface layer of the coating film, leaving the cuprous oxide particles and binder resin present in the lower layer of the coating film, and reducing damage to the substrate.
[0040] The number of times of irradiation with pulsed light is not particularly limited as long as the cuprous oxide particles present in the surface layer of the coating film can be sufficiently reduced and sintered while the cuprous oxide particles and binder resin present in the lower layer of the coating film can be left behind, and the same irradiation pattern may be repeated, or various irradiation patterns may be repeated several times. From the viewpoint of productivity and damage to the substrate, it is preferable to reduce and sinter the coating film by irradiation five times or less, but this is not limited depending on the type of substrate.
[0041] The atmosphere in which the pulsed light irradiation is performed is not particularly limited, and may be any of the air atmosphere, an inert gas atmosphere, a reducing gas atmosphere, and the like.
[0042] In the method for forming a conductive film of the present invention, in order to improve the adhesion between the obtained conductive film and the substrate, it is preferable to compress the conductive film formed on the substrate, and more preferably, the compression is performed by applying pressure with a roll. A roll press machine can be used for the compression. The conditions for applying pressure to the conductive film may be appropriately determined, but from the viewpoint of improving the adhesion to the substrate, a linear pressure of 100 to 30,000 kN / m is preferable.
[0043] An embodiment of the present invention includes the following. [1] A conductive film formed on a substrate, the conductive film is made of a photoreduced sintered product of a composition containing cuprous oxide particles and a binder resin; an unsintered layer is formed between the substrate and the conductive film, the unsintered layer including cuprous oxide particles and a binder resin that have not been photoreduced, The conductive film, wherein the carbon molar fraction in the molecule of the binder resin is 0.15% to 0.9% and the oxygen molar fraction is 0.03% to 0.2%. [2] The conductive film according to [1], wherein the cuprous oxide particles contain at least one additive element selected from the group consisting of tin, manganese, vanadium, cerium, and silver. [3] The conductive film according to [2], wherein the additive element is tin and the content thereof is 150 ppm to 3000 ppm. [4] The conductive film according to any one of [1] to [3], wherein the cuprous oxide particles have an average primary particle diameter of 1 nm to 2000 nm. [5] The conductive film according to any one of [1] to [4], wherein the binder resin has a 50% weight loss temperature of 300°C to 500°C. [6] The conductive film according to any one of [1] to [5], wherein the binder resin contains at least one selected from the group consisting of a cellulose resin, a polyvinyl resin, an unsaturated polyester resin, a saturated polyester resin, a terpene phenol resin, an acrylic resin, a polyurea resin, a polyurethane resin, a polyether resin, and an epoxy resin. [7] The conductive film according to any one of [1] to [6], wherein the binder resin contains at least one selected from the group consisting of methyl cellulose, ethyl cellulose, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl acetate, polymethyl(meth)acrylate, polyethyl(meth)acrylate, polyethylene glycol, and polypropylene glycol. [8] The composition has a volume resistivity of 1.0 × 10 at 20 ° C. -3 The conductive film according to any one of [1] to [7], further comprising metal particles having a resistivity of Ω·cm or less. [9] The conductive film according to [8], wherein the metal particles are particles of at least one type of metal selected from the group consisting of gold, silver, copper, zinc, tin, aluminum, nickel, cobalt, and manganese.
[10] The conductive film according to any one of [1] to [9], wherein the base material is paper or polyethylene terephthalate.
[11] A method for forming a conductive film on a substrate, comprising the steps of: A step of applying a composition containing cuprous oxide particles and a binder resin to a substrate to form a coating film; a step of irradiating the coating film with light to photo-reduce and sinter the cuprous oxide particles in the coating film to form a conductive film, while forming an unsintered layer between the base material and the conductive film, the unsintered layer including the cuprous oxide particles and the binder resin that have not been photo-reduced and remain; Equipped with The method for forming a conductive film, wherein the carbon molar fraction in the molecule of the binder resin is 0.15% to 0.9% and the oxygen molar fraction is 0.03% to 0.2%.
[12] The method for forming a conductive film according to
[11] , wherein the substrate is paper or polyethylene terephthalate.
[13] The method for forming a conductive film according to
[11] or
[12] , further comprising compressing the conductive film formed on the substrate. EXAMPLES
[0044] The present invention will be described below with reference to examples, but the present invention is not limited to these examples.
[0045] <Preparation of Cuprous Oxide Particles 1> 25.0 g of a 48% by mass aqueous sodium hydroxide solution and 100.0 g of pure water were added to a 500 mL reaction vessel, and the temperature inside the reaction vessel was adjusted to 40° C. while stirring the contents inside the reaction vessel to prepare an alkaline solution. On the other hand, 17.3 g (0.1 mol) of copper(II) chloride dihydrate, 80.0 g of pure water, and 0.45 g (0.002 mol) of tin(II) chloride dihydrate as a divalent tin ion source were added to a 100 mL glass beaker to prepare an aqueous solution containing copper ions and divalent tin ions. While maintaining the temperature inside the reaction vessel at 40°C, the aqueous solution containing copper ions and divalent tin ions was added to the reaction vessel over about 2 minutes, and then stirred for 10 minutes to precipitate copper hydroxide.
[0046] A reducing agent solution was prepared by adding 10.0 g of glucose and 15.0 g of pure water to a 100 mL glass beaker. This reducing agent solution was added to the reaction vessel over about 30 seconds, and then the temperature in the reaction vessel was raised to 50°C and maintained for 15 minutes. Thereafter, stirring in the reaction vessel was stopped, and the slurry was filtered and washed to prepare a cake. This cake was vacuum-dried at 80°C for 3 hours to obtain cuprous oxide particles 1.
[0047] The average primary particle diameter of the obtained cuprous oxide particles 1 was determined to be 0.1 μm from an image of the obtained cuprous oxide particles 1 observed by an electron microscope (SEM). The tin content of the cuprous oxide particles 1 was 570 ppm.
[0048] <Examples 1 to 10 and Comparative Examples 1 to 4> The cuprous oxide particles 1 obtained above were used to prepare each composition and form a conductive film. Specifically, cuprous oxide particles 1, binder resin, and butyl carbitol as an organic solvent were kneaded at atmospheric pressure for 30 minutes at 1,000 rpm using a kneader in the proportions shown in Table 1 to prepare a paste-like composition. The paste-like composition was screen-printed on a paper substrate (SWORD, manufactured by Mitsubishi Paper Mills, thickness 50 μm) to form a rectangular pattern of 1 mm × 20 mm to form a coating film. The coating film was dried at 80 ° C for 10 minutes in an atmospheric atmosphere. A pulsed light was irradiated to the coating film formed on the paper substrate with one pulse (voltage: 2700 V, pulse width: 2000 microseconds) using a xenon pulsed light irradiation device (S-2300, manufactured by Zenon Corporation) so that the pulsed light irradiation energy was the value shown in Table 1, to form a conductive film. Next, the conductive film and the substrate were passed through a roll press (steel rolls with a diameter of 60 mm) at a linear pressure of 1000 kN / m and a roll peripheral speed of 10 mm / s to apply pressure, thereby carrying out a compression treatment. However, in Comparative Example 4, the fluororesin used as the binder resin was not dissolved in the organic solvent, so a coating film could not be formed.
[0049] [Table 1]
[0050] <Preparation of Cuprous Oxide Particles 2> 25.0 g of a 48% by mass aqueous sodium hydroxide solution and 100.0 g of pure water were added to a 500 mL reaction vessel, and the temperature inside the reaction vessel was adjusted to 40° C. while stirring the contents inside the reaction vessel to prepare an alkaline solution. On the other hand, 17.3 g (0.1 mol) of copper(II) chloride dihydrate, 80.0 g of pure water, and 0.49 g (0.002 mol) of manganese(II) acetate tetrahydrate as a divalent manganese ion source were added to a 100 mL glass beaker to prepare an aqueous solution containing copper ions and divalent manganese ions. While maintaining the temperature inside the reaction vessel at 40°C, the aqueous solution containing copper ions and divalent manganese ions was added to the reaction vessel over about 2 minutes, and then stirred for 10 minutes to precipitate copper hydroxide.
[0051] A reducing agent solution was prepared by adding 10.0 g of glucose and 15.0 g of pure water to a 100 mL glass beaker. This reducing agent solution was added to the reaction vessel over about 30 seconds, and then the temperature in the reaction vessel was raised to 50°C and maintained for 15 minutes. Thereafter, stirring in the reaction vessel was stopped, and the slurry was filtered and washed to prepare a cake. This cake was vacuum-dried at 80°C for 3 hours to obtain cuprous oxide particles 2.
[0052] The average primary particle diameter of the obtained cuprous oxide particles 2 was determined to be 0.1 μm from an image of the obtained cuprous oxide particles 2 observed by an electron microscope (SEM). The manganese content in the cuprous oxide particles 2 was 2180 ppm.
[0053] <Examples 11 to 14 and Comparative Examples 5 to 6> The cuprous oxide particles 2 obtained above were used to prepare each composition and form a conductive film. Specifically, cuprous oxide particles 2, copper particles (Mitsui Mining & Smelting Co., Ltd., 1100Y, average particle size 1.1 μm), binder resin, and butyl carbitol as an organic solvent were kneaded at atmospheric pressure for 30 minutes at 1,000 rpm using a kneader in the proportions shown in Table 2 to prepare a paste-like composition. The paste-like composition was printed on a polyethylene terephthalate substrate (Toray Industries, Inc., Lumirror S10, thickness 50 μm) by screen printing to form a rectangular pattern of 1 mm x 20 mm. The coating film was dried at 80°C for 10 minutes in an atmospheric atmosphere. A pulsed light was irradiated to the coating film formed on the polyethylene terephthalate substrate using a xenon pulsed light irradiation device (Zenon Corporation, S-2300) for one pulse so that the pulsed light irradiation energy was the value shown in Table 2 (voltage: 2700 V, pulse width: 2000 microseconds), to form a conductive film. Next, the conductive film was subjected to a compression treatment by passing it together with the substrate between a roll press machine (steel rolls having a diameter of 60 mm) at a linear pressure of 1000 kN / m and a roll peripheral speed of 10 mm / s.
[0054] [Table 2]
[0055] <Printability evaluation> A wiring pattern was printed on the substrate by screen printing, and the printout was observed under a microscope and evaluated for appearance according to the following criteria. A wiring pattern without any defects was judged to have "excellent" printability, a wiring pattern with some defects was judged to have "good" printability, and a wiring pattern with breaks or bleeding was judged to have "poor" printability. The results are shown in Table 3.
[0056] <Sinterability evaluation> The conductive film formed was judged to have excellent sinterability if it was uniform and free of defects, to have good sinterability if it had some defects due to scattering of the conductive film or some unsintered parts, and to have defects due to scattering of the conductive film or unsintered parts if it had poor sinterability. The results are shown in Table 3.
[0057] <Adhesion evaluation> After applying tape to the conductive film, the tape was peeled off, and if the conductive film was not attached to the adhesive surface of the tape and the conductive film formed on the paper base remained intact, the adhesion was judged to be "excellent," if the conductive film was attached to part of the adhesive surface of the tape but there were no breaks in the conductive film, the adhesion was judged to be "good," and if the conductive film was attached to the adhesive surface of the peeled tape and there were breaks in the conductive film, the adhesion was judged to be "poor." The results are shown in Table 3.
[0058] <Thickness of conductive film and unsintered layer> The cross section of the conductive film formed on the paper substrate was subjected to EDS elemental mapping analysis of copper, oxygen and carbon elements using a scanning electron microscope (SEM), the boundary between the substrate and the unsintered layer and the boundary between the conductive film and the unsintered layer were determined, and the thickness of the conductive film and the unsintered layer were obtained. Figure 1 shows an SEM image of the cross section of the conductive film formed on the substrate in Example 2, and an EDS elemental mapping image of copper, oxygen and carbon elements.
[0059] [Table 3]
[0060] As can be seen from the results in Table 3, the conductive films of Examples 1 to 14 had excellent adhesion to the substrate. On the other hand, the conductive films of Comparative Examples 1 to 6 had poor adhesion to the substrate.
Claims
1. A conductive film formed on a substrate, the conductive film is made of a photoreduced sintered product of a composition containing cuprous oxide particles and a binder resin; an unsintered layer is formed between the substrate and the conductive film, the unsintered layer including cuprous oxide particles and a binder resin that have not been photoreduced, The conductive film, wherein the carbon molar fraction in the molecule of the binder resin is 0.15% to 0.9% and the oxygen molar fraction is 0.03% to 0.2%.
2. The conductive film according to claim 1 , wherein the cuprous oxide particles contain at least one additive element selected from the group consisting of tin, manganese, vanadium, cerium, and silver.
3. 3. The conductive film according to claim 2, wherein the added element is tin and the content thereof is 150 ppm to 3000 ppm.
4. The conductive film according to claim 1 or 2, wherein the cuprous oxide particles have an average primary particle diameter of 1 nm to 2000 nm.
5. 3. The conductive film according to claim 1, wherein the binder resin has a 50% weight loss temperature of 300° C. to 500° C.
6. 3. The conductive film according to claim 1, wherein the binder resin comprises at least one selected from the group consisting of a cellulose resin, a polyvinyl resin, an unsaturated polyester resin, a saturated polyester resin, a terpene phenol resin, an acrylic resin, a polyurea resin, a polyurethane resin, a polyether resin, and an epoxy resin.
7. 3. The conductive film according to claim 1, wherein the binder resin comprises at least one selected from the group consisting of methyl cellulose, ethyl cellulose, polyvinylpyrrolidone, polyvinyl alcohol, polyvinyl acetate, polymethyl (meth)acrylate, polyethyl (meth)acrylate, polyethylene glycol, and polypropylene glycol.
8. The composition has a volume resistivity of 1.0×10 -3 The conductive film according to claim 1 or 2, further comprising metal particles having a resistivity of Ω·cm or less.
9. 9. The conductive film according to claim 8, wherein the metal particles are at least one type of metal particles selected from the group consisting of gold, silver, copper, zinc, tin, aluminum, nickel, cobalt, and manganese.
10. The conductive film according to claim 1 or 2, wherein the substrate is paper or polyethylene terephthalate.
11. A method for forming a conductive film on a substrate, comprising the steps of: A step of applying a composition containing cuprous oxide particles and a binder resin to a substrate to form a coating film; a step of irradiating the coating film with light to photo-reduce and sinter the cuprous oxide particles in the coating film to form a conductive film, while forming an unsintered layer between the base material and the conductive film, the unsintered layer including the cuprous oxide particles and the binder resin that have not been photo-reduced and remain; Equipped with The method for forming a conductive film, wherein the carbon molar fraction in the molecule of the binder resin is 0.15% to 0.9% and the oxygen molar fraction is 0.03% to 0.2%.
12. The method for forming a conductive film according to claim 11 , wherein the substrate is paper or polyethylene terephthalate.
13. The method for forming a conductive film according to claim 11 or 12, further comprising the step of compressing the conductive film formed on the substrate.
Citation Information
Patent Citations
Metallic ink
JP2014116315A
Photosintering composition, and method of forming conductive film using the same
JP2019149360A
Photosintering composition and method of forming conductive film using the same
JP2019200912A
Conductive paste, base material with conductive film, production method of base material with conductive film
JP2020119737A
Conductive-pattern formation method and composition for forming conductive pattern via light exposure or microwave heating
WO2013077448A1